The Influence Of Diet On Quality Nutrition Counselling Patients Of Type 2 Diabetes Mellitus In Poly Disease In The RSUD Dr.M. Yunus Bengkulu 2018 - Rossy Tri Pertiwi; Emy Yuliantin; Anang Wahyudi (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2018)
Nutritional counseling is one of the efforts of the medical nutrition therapy provided to improve the diet and lifestyle of patients of diabetes mellitus.One of the key factors in the treatment of the disease of diabetes mellitus is an improvement of the quality of the diet.The purpose of this research is to know the influence of diet on quality nutrition counselling patients of diabetes mellitus in poly disease in the RSUD dr.M. Yunus Bengkulu year 2018. This type of research is pre-circling with pre and posttest one gorup design.This research was carried out from April to may 2018. The location of the research on poly disease in the RSUD dr.M. Yunus Bengkulu. research Sample is selected by purposive sampling in accordance with the criteria of inclusion and ekslusi.The number of samples that is 20 respondents. The data are tested using the kolmogorov smirnov test, wilcoxon. The results of the research there is a meaningful influence obtained between nutritional counseling to the quality of the patient's diet diabetes mellitus type II in Poly disease in the RSUD dr.M. Yunus Bengkulu Year 2018 with (p = 0.006). Expected to further researchers can continue research on diabetes mellitus patients with more samples to make it more visible variations in the quality of diet of diabetes mellitus patients and researchers can then tried a more educational media varied to seek effectiveness in the media.